2011
DOI: 10.1001/archsurg.2011.176
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Site Infections in Colon Surgery

Abstract: To determine the role of the surgeon in the occurrence of surgical site infection (SSI) following colon surgery, with respect to his or her adherence to guidelines and his or her experience. Design, Setting, and Patients: Prospective cohort study of 2393 patients who underwent colon surgery performed by 31 surgeons in 9 secondary and tertiary care public Swiss hospitals, recruited from a surveillance program for SSI between March 1, 1998, and December 31, 2008, and followed up for 1 month after their operation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
34
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(37 citation statements)
references
References 48 publications
3
34
0
Order By: Relevance
“…The rates of superficial and deep wound infection noted in the present study are similar to data published by Hawn et al [19] and Tang et al [20], and compare favourably to values reported in several earlier publications [21-23]. Male sex, obesity, specific surgeons or hospitals, ostomy and total/subtotal colectomy were identified as risk factors for surgical site infection after colorectal surgery [22-25]. The circumscript number of cases present in our cohort did not allow subgroup analysis with regard to any technical aspects associated with SSI.…”
Section: Discussionsupporting
confidence: 91%
“…The rates of superficial and deep wound infection noted in the present study are similar to data published by Hawn et al [19] and Tang et al [20], and compare favourably to values reported in several earlier publications [21-23]. Male sex, obesity, specific surgeons or hospitals, ostomy and total/subtotal colectomy were identified as risk factors for surgical site infection after colorectal surgery [22-25]. The circumscript number of cases present in our cohort did not allow subgroup analysis with regard to any technical aspects associated with SSI.…”
Section: Discussionsupporting
confidence: 91%
“…8,10,22,23 Important factors affecting this variation are differences in clinical case definition, 24 differences in definition based on billing information (in our study we varied between ICD-9 codes and billing for wound cultures), and follow-up time. 25,26 Indeed, 50% of SSI cases have been shown to occur after discharge 26 and, thus, were not captured in our data. Importantly, however, this underestimation is likely to be distributed equally among all types of antibiotic prophylaxis.…”
Section: Discussionmentioning
confidence: 94%
“…The overall incidence rate of surgical site infection following bowel surgery was observed to range between 5.8 and 17.9 % [2022]. SSI rate following bowel surgery using BAR anastomosis was reported to be lower and ranging between 4.7 and 5.0 % in large series [7, 8, 13].…”
Section: Discussionmentioning
confidence: 99%